La recherche de l’âme soeur à l’heure des Technologies de l’Information et de la Communication : l’exemple des Camerounaises - Baba Wame (Tic & Société)
Almost unknown about some 15 years ago, the Internet knew a remarkable breakthrough in Cameroon. The principal access points of the public to the Internet, the cyber cafés are literarily taken hostage by Cameroonian women. They are called “tchatteuse”. The have invaded dating web sites. They are between 18 and 34 years old, with a low educational level. Not all are single far from that, some are married and surf the Internet with the agreement of their husbands. They expected to change their life by getting a husband on dating web sites. The half cast children like Yannick Noah, have a valued image in Cameroon are also expected through the marriage with white men. Unfortunately, only few of Cameroonian women get a husband through the dating web sites. 60% of these women become later prostitutes.